Dentals Chair's evolution with the incorporation of ergonomics elements - Tânia Adas Saliba; Maria Elizabeth Peña Téllez; Artênio José Isper Garbin; Cléa Adas Saliba Garbin (Editorial Ciencias Médicas, 2018)
Introduction: The development of science has enabled the production of equipment that benefits the health of human beings. Over the course of time, the manufacturing of dental chairs has followed protocols in order to ensure the comfort of the patient and the professional. Objective: To describe the evolution of the dental chair and the application of international standards for its design and manufacture. Method: This is a descriptive study, of historical series. The data was obtained from the existing historical documentation and photographic images in the scientific literature, articles were consulted on websites, BBO, Lilacs and Medline, all related to the research topic. Results: Dental chairs showed a significant evolutionary tendency in the last years: at the beginning of the dental practice, they allowed the work with the patient sitting, then they appeared with different positions in the back and with the passage of time there was an increase of the devices and control of movements of head, arms, seat and back, making possible activities with the patient lying down. In the process of the evolution of the chairs, in relation to their design and construction, international standards are followed to guarantee the quality and comfort of these, which has been satisfactory in the reduction of musculoskeletal affectations of the dentist professionals. Conclusions: Despite of the existence of the new established technologies, it is necessary to continue incorporating ergonomic elements that produce maximum comfort to the professional and the patient in order to optimize the dental work.